The effect of 20 repetitions badminton footwork training on increasing maximum oxygen volume (VO2Max) - I Putu Astrawan; I Made Dhita Prianthara; I A Pascha Paramurthi (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Footwork is foot movements that regulate the body to position the body in such a way that makes it easier to make the movement to hit the shuttlecock according to its position. The type of quasi-experimental research with the design used in this research is "Pre-Test and Post-Test One Group Design". Researchers looked for samples in one group that received the same treatment and were given 20 repetitions of badminton footwork training. The research sample was a total sampling involving all 15 male athletes at UKM Badminton. The percentage increase in maximum oxygen volume in the training group for four weeks shows that the maximum oxygen volume increased after treatment. The percentage increase in maximum oxygen volume in group training was 30.25%. Can be conluded Badminton Footwork Training 20 Repetition Can Increase Maximum Oxygen Volume (VO2Max) in Badminton UKM Male Athletes at Bali International University in 2024.